Chronic Toxicity Study of the Substance "Branched ohgo(hexamethylene guanidine) hydrochloride" During Oral Irrigation - S. V. Belyakov; S. А. Kedik; D. O. Shatalov; D. A. Akhmedova; P. Yu. Demenyuk (Антибиотики и Химиотерапия)
The study of the chronic toxicity of the substance «Branched oligo(hexamethylene guanidine) hydrochloride» was carried out with repeated (within 28 days) irrigation of the oral cavity of rats and rabbits. During the experiment, observations were made of the general condition and behavioral activity of animals, feed and water consumption, coat condition, and body weight dynamics. The state of homeostasis was evaluated using functional, hematological, biochemical and pathomorphological methods. According to research results, it was found that the substance during irrigation of the oral cavity of rats at doses of 0.78 mg/kg and 15.6 mg/kg, as well as rabbits at doses of 0.34 mg/kg and 6.8 mg/kg, did not cause significant changes in the clinical condition of animals.